2017
DOI: 10.18632/oncotarget.23663
|View full text |Cite
|
Sign up to set email alerts
|

Developing a genetic signature to predict drug response in ovarian cancer

Abstract: There is a lack of personalized treatment options for women with recurrent platinum-resistant ovarian cancer. Outside of bevacizumab and a group of poly ADP-ribose polymerase inhibitors, few options are available to women that relapse. We propose that efficacious drug combinations can be determined via molecular characterization of ovarian tumors along with pre-established pharmacogenomic profiles of repurposed compounds. To that end, we selectively performed multiple two-drug combination treatments in ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 82 publications
0
7
1
Order By: Relevance
“…Additionally, Trx has been found to activate the PI3K/AKT pathway [ 40 ], which in turn promotes cell proliferation, migration, and survival by phosphorylating and inactivating several key apoptotic molecules such as Bad, procaspase-9, and FKHR1(forkhead box protein 1) [ 51 ]. Recently, it was reported that auranofin alone or in combination with other drugs targeting TrxR can induce apoptosis through inhibition of the AKT pathway [ 29 , 52 , 53 , 54 , 55 ]. Similarly, the AKT pathway has been proven to take part in the apoptotic cell death induced by the auranofin-related compound chloro(triethylphosphine)gold(I) [ 56 ] and an N-heterocyclic carbene–gold(I) complex [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Trx has been found to activate the PI3K/AKT pathway [ 40 ], which in turn promotes cell proliferation, migration, and survival by phosphorylating and inactivating several key apoptotic molecules such as Bad, procaspase-9, and FKHR1(forkhead box protein 1) [ 51 ]. Recently, it was reported that auranofin alone or in combination with other drugs targeting TrxR can induce apoptosis through inhibition of the AKT pathway [ 29 , 52 , 53 , 54 , 55 ]. Similarly, the AKT pathway has been proven to take part in the apoptotic cell death induced by the auranofin-related compound chloro(triethylphosphine)gold(I) [ 56 ] and an N-heterocyclic carbene–gold(I) complex [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using a high-throughput viability screen and reliable in silico data allowed the rational identification of two pathways that can lead to synergistic interaction towards cell death in ovarian cancer. The study discovered that the TrxR inhibitor and ROS inducer auranofin synergized in the killing of ovarian cancer cells with the heat-shock protein 90 (HSP90) chaperone antagonist, AUY922 [ 112 ].…”
Section: Auranofin Anti-cancer Activity In Combination Treatmentsmentioning
confidence: 99%
“…Oommen et al demonstrated that in OVCAR5 and SKOV3 cells, BRCA1 silencing increased AF cytotoxicity and that AF‐induced DNA double strand brakes in a ROS‐dependent manner, thus demonstrating that BRCA1 deficiency renders tumor cells more sensitive to AF 112 . Hyter et al tested the cytotoxicity of AF alone or in combination with HSP90 inhibitors in ten ovarian cancer cell lines founding that there were remarkable differences in AF sensitivity in different lines 113 . They utilized A1847 and PEO4 as representative cell lines for the sensitive and resistant groups respectively and they demonstrated a synergic effect of AF and the HSP90 inhibitor AUY922.…”
Section: Af Repurposing In Cancer Therapymentioning
confidence: 99%